Assessment of Natural Radioactive Nuclides Variability and Distribution in Soils of Pokhara, Nepal (Bangladesh Journal of Physics, 2026)
The purpose of this study is to determine the radioactivity concentrations of K-40, Th-232, U-238, and Radiological Equivalent (Raeq) in soil samples from Pokhara, Nepal. The measurements were performed using a NaI(Tl) detector and Gamma Vision software. The results show that the average radioactivity concentrations of K-40 were detected at 463.00 Bq/kg, Th-232 at 69.20 Bq/kg, and U-238 at 52.80 Bq/kg. Based on these concentrations, the average radioactivity concentration Raeq was determined at 187.00 Bq/kg, which is less than the UNSCEAR safety limit of 370 Bq/kg. The Hazard Index (H) derived from measurements of K-40, Th-232, and U-238 was 0.51-0.65, which is less than the global average of 1. The Annual Effective Dose Equivalent (AEDE) was computed based on measurements 0.11-0.13, which remained below the global average limit of 1 mSv/year. The measured result yielded an estimated Excess Lifetime Cancer Risk (ELCR) of 0.39-0.44 × 10⁻³, somewhat higher than the recommended range of 0.29 × 10⁻³. The standard error for all measurements in this study is ±0.04 counts per minute.Bangladesh Journal of Physics, Vol. 32, Issue 2, pp. 13 – 27, December 2025